A family of putative potassium channel genes in Drosophila. - Butler, A.; Wei, A.G.; Baker, K.; Salkoff, L. (Science, 1989)
Mutant flies in which the gene coding for the Shaker potassium channel is deleted still have potassium currents similar to those coded by the Shaker gene. This suggests the presence of a family of Shaker-like genes in Drosophila. By using a Shaker complementary DNA probe and low-stringency hybridization, three additional family members have now been isolated, Shab, Shaw, and Shal. The Shaker family genes are not clustered in the genome. The deduced proteins of Shab, Shaw, and Shal have high homology to the Shaker protein; the sequence identity of the integral membrane portions is greater than 50 percent. These genes are organized similarly to Shaker in that only a single homology domain containing six presumed membrane-spanning segments common to all voltage-gated ion channels is coded by each messenger RNA. Thus, potassium channel diversity could result from an extended gene family, as well as from alternate splicing of the Shaker primary transcript.